PENERAPAN COLLABORATIVE LEARNING ALAM SEKOLAH INKLUSI DI SMP DIPONEGORO BATU - Aprilia Ema Wardhani; Asep Sunandar; Asim Asim; Mohammad Efendi; Ahmad Samawi; Ediyanto Ediyanto (Universitas Muria Kudus, 2022)
The purpose of this study was to determine the implementation of collaborative learning given by teachers to children with special needs in inclusive schools at the junior high school level.The research method used is descriptive with a qualitative approach, while data collection uses observation, interviews, and documentation techniques for three teachers at SMP Diponegoro Batu.The results of the study indicate that the application of Collaborative learning given to children with special needs has been implemented quite well. This good implementation can be seen from the existence of special supervisor teachers from schools, the acceptance of students from various disabilities, and cooperation between classroom teachers and special supervisors. This collaboration makes the achievement of learning objectives in a class where there are normal students and students with special needs